Deflections and Strains in Cracked Shafts due to Rotating Loads: A Numerical and Experimental Analysis. (2004) - Bachschmid, N.; Tanzi, E.
Abstract : In this article, the deflections of a circular cross-section beam presenting a transverse crack of different depths, due to different loads (bending, torsion, shear, and axial loads), are analyzed with the aid of a rather refined 3-D model, which takes into account the nonlinear contact forces in the cracked area. The bending and shear loads are applied in several different angular positions, in order to simulate a rotating load on a fixed beam, or, by changing the reference system, a fixed load on a rotating beam. Torsion and axial loads are instead fixed with respect to the beam. Results obtained for the rotating beam can then be used for the analysis of cracked, horizontal axis heavy rotors, in which the torsion is combined to the bending load. The effect of friction is also considered in the cracked area. The characteristic "breathing" behavior of the cracked area has been analyzed and compared to that one obtained with a rather simple 1-D model. The differences in results with respect to those which can be obtained by means of the approach based on fracture mechanics are emphasized. In order to highlight the effect of the presence of the crack, the deflections of the uncracked beam loaded with the same loads are subtracted from the deflections of the cracked beam. Finally, a cracked specimen has been extensively analyzed by means of several strain gauges, for analyzing the strain distribution on the outer surface around the crack, in different loading conditions. Consistent pre-stresses have been found, which influence the breathing behavior. The experimental results have been compared to those obtained with the 1-D linear model.